Vocabulary techniques to improve english writing skills, to students of eighth year at Presidente Tamayo School, Salinas, Santa Elena province. 2017-2018. - Alvarado De La Torre, Tanny Alexandra (2018)
Nowadays it is very important to learn English effectively and to master all of its skills, the focus of this research project will be aimed at improving the writing skills with vocabulary techniques. In order to improve writing skills it is very important for educators and students the implementation of interesting vocabulary techniques inside the classrooms to make the learning – teaching process a great experience while improving writing. During the field research done at Presidente Tamayo School in Salinas there are problems in the learning English skills, but can be reinforced with appropriate methods. This project shows the improvement of eighth grade from President Tamayo School through vocabulary techniques that encourage students to develop their overall English fluency. Activities such as brainstorming, pre-writing, scanning, skimming, describing people, routines, and vocabulary related to occupations, daily activities, music, adjectives, verbs, food and more will be the basis in which this work is structured.